The Phenomenon “Scenic Culture” of a Musician Student: Content Structure as a Basis for Diagnosis - Zhu, Lu (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The aim of the article is to generalize the essence of the phenomenon of “stage culture” in the projection onto the context of the musician-performer’s activity. The task is outlined to determine, in the specified context, the content-component structure of the phenomenon for further monitoring of its development among students of art faculties. Stage culture is considered as a component of “culture” and “artistic-aesthetic culture” and contains the main factors: artistic-aesthetic consciousness, which is humanized in artistic activity. The interdependence among these factors is shown. The starting point of the analysis is outlined: the definition of “stage culture” also contains two core components: “culture” in the broad sense and the projection of its essence into the artistic plane, where the reference point for determining the content is “stage”. The concepts common to all types of stage actions are considered – stage space, stage artistic image, artistic communication. It is recognized that “stage culture” primarily concerns various forms of theatrical art. However, it is shown that the musical stage image is also a stage art and has a dual nature: the image of the performer who communicates with the audience, and the image of the musical work that the performer interprets. The definition of stage culture is formulated as a component of aesthetic culture and a polystructural integral personal quality of a musician – the subject of stage performance and stage musical artistic image. The structural components of the content of the stage culture of a performer-musician are distinguished: axiological (values, emotionality of perception and transmission of speech, value attitude to one’s own performance), cognitive (artistic erudition, polyartistic aspects), activity (performance-interpretation and activity-communicative), motivational (motivation, which is present in the content of each component).